Neat in theory, entangled in praxis: A practice perspective on the social notion of collective reflection in organisations. Issue 3 (July 2019) - Gutzan, Simone; Tuckermann, Harald
Although scholars have begun theorising the social notion of collective reflection in organisations, empirical studies illustrating these often neat theoretical conceptualisations are still rare. Based on a longitudinal case study (the introduction of lean production at an emergency care unit), we address this need by applying a practice approach. Collective reflection in the present empirical case is manifold: it is characterised by several activities, each serving a specific purpose and enacted according to different temporal rhythms. Our inductive theorising broadens the theoretical conceptualisation of collective reflection in organisations. We propose value creation as a 'point of reference', in order to account for what exactly actors step back from when collectively reflecting. We found that collectively reflecting in organising means creating multiple local co-presences. We suggest that the current conceptualisation of collective reflection as a discursive practice itself calls for empirical substantiation.